Penggunaan Media Komik Digital Interaktif Terhadap Motivasi Belajar Siswa Kelas IV SD Materi Keberagaman Budaya di Indonesia - Marcella Nurul Annisa; Tin Rustini (PT. ALHAFI BERKAH INDONESIA, 2023)
The complexity of the various materials can make it difficult for students to understand the lesson. Many students feel bored when studying material about Indonesia's diversity, especially if the learning media does not interest them. Therefore, it is hoped that this interactive cartoon comic learning media about Indonesia's diversity can be a solution to increase the motivation and learning efficiency of 4th grade elementary school students. This research uses a type of library research that involves presenting qualitative interpretive data, and the main audience consists of various available library books. There are several benefits to using interactive digital comics in learning. This media helps students understand learning material by interacting in an interesting and informative manner and this media can increase students' interest in learning because it can help their development and increase their learning motivation. This media contains many interesting pictures and stories, which increase students' creativity and imagination and improve students' reading comprehension. This media helps teachers convey learning material in a way that makes the learning process meaningful, thereby increasing learning efficiency. This media improves student learning outcomes. Arranging teaching materials in a more interesting and interactive way will improve the quality of learning because this media helps teachers explore creativity and innovation in various learning media. From the research results, it can be concluded that the use of interactive digital comics can increase the motivation of 4th grade elementary school students in studying material about diversity in Indonesia.